Failure mechanism and reliability analysis of the rear cargo door lock of transport aircraft. (April 2021) - Sun, Zhongchao; Yu, Tianxiang; Pang, Huan; Song, Bifeng
Highlights: The failure mechanism of the cargo door lock is analyzed and the root cause is found. The critical factors are identified based on reliability sensitivity analysis. Improvement measures are proposed and they have been proved effective. Abstract: The cargo door lock is a critical component of the rear cargo door system of transport aircraft. Malfunction of the cargo door lock may lead to airdrop mission failure or even catastrophic accident. In the reliability test of the rear cargo door system of a transport aircraft, one of the cargo door locks failed to open. However, the failure cannot be remedied by simply strengthening the failed parts. In this work, we analyze the failure mechanism to find out the root cause. Then, the open function reliability is assessed and the local as well as the global reliability sensitivity analysis are performed to interrogate the impacts of the random influence factors. On this basis, the critical random influence factors are identified and accordingly the improvement measures are proposed. After the failed cargo door lock is improved based on the improvement measures, the open function failure didn't occur again in the subsequent test, verifying the effectiveness of the proposed improvement measures.